Preparation of Graphene Oxide from Expanded Graphite at Different Microwave Heating Times - Ahmed A Moosa; Zainab H. Mahdi; Mohammed A. Mutar (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Exfoliated graphite (EG) was prepared by mixing graphite with HNO3 and KMnO4 at weight ratio 1:2:1 using microwave heating at times 20, 60, 80 and 120 sec. Graphene oxide (GO) was then prepared using EG as precursor by the modified Hummer’s method. Atomic force microscopy (AFM), X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy analyses showed successful conversion of EG into GO. The XRD results of the GO showed that the maximum interplanar distance (d-spacing) increased from 0.344 to 0.831 nm. The AFM showed a minimum thickness of 0.519 nm for a single layer of GO prepared from EG 80 sec. The XRD examination also showed an increase in the d-spacing between the GO layers after sonication compared to before sonication.